TREATMENT OF PATHOLOGIES IN PREGNANT WOMEN AND ENSURING CARE WITHOUT COMPLICATIONS (CAHIERS MAGELLANES-NS, 2024)
In organize to guarantee the mother's and the fetus's victory and security inside the center of pregnancy, pathologies must be treated. The ask for evidence-based drugs to sensibly facilitate steadfast sufferings has opened up due to the progress in these conditions among women of childbearing age. This article highlights the regard of a multidisciplinary approach to care, looks at organization strategies, and looks at the open up of visit torments that influence certain mothers. Case considers arrange beneficial organization strategies to guarantee trouble-free maternal-fetal flourishing.